The Challenge of Democracy in the Muslim World - Darmadi, Dadi (Studia Islamika, 2002)
Is it true that in the Muslim world the more Islamic a country is the less likely it is to be democratic? This type of question may sound empirical data produced by the Freedom House (2001) discloses this tendency. Out of 47 countries in the world with Muslim majorities, only 11 (or 23 per cent) can be regarded as haring truly adopted-democracy and have gone through a relatively stable period of the-consolidation of democracy. Meanwhile, in the non-Muslim world, 110 out of 145 countries (more than 75 per cent) have democratically elected governments. We may draw the conclusion from this data that in the non-Muslim world, a country is three times more likely to be democratic than one in the Muslim world.DOI: 10.15408/sdi.v9i1.679